2021
DOI: 10.1155/2021/5599374
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils from Thymus capitatus and Thymus algeriensis as Antimicrobial Agents to Control Pathogenic and Spoilage Bacteria in Ground Meat

Abstract: The antibacterial effects of essential oils (EOs) extracted from Thymus capitatus and Thymus algeriensis were assessed and evaluated against four pathogenic bacteria (Escherichia coli (ATCC 25922), Listeria monocytogenes (ATCC 19118), Staphylococcus aureus (ATCC 25923), and Salmonella typhimurium (ATCC 1402)) and one spoilage bacterium (Pseudomonas aeruginosa (ATCC 27853)). Both investigated EOs presented significant antimicrobial activities against all tested bacteria with a greater antibacterial effect of T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In addition, the evaluated EO caused a decrease in the growth of E. coli within the first ten minutes. Our data corroborate a previous study about the rapid antibacterial effect of T. capitatus EO against E. coli –BLSE producers [ 17 , 29 ], probably because it contained a high concentration of carvacrol and thymol. Xu et al [ 39 ] showed that carvacrol is able to embrittle and depolarize the cytoplasmic membrane.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the evaluated EO caused a decrease in the growth of E. coli within the first ten minutes. Our data corroborate a previous study about the rapid antibacterial effect of T. capitatus EO against E. coli –BLSE producers [ 17 , 29 ], probably because it contained a high concentration of carvacrol and thymol. Xu et al [ 39 ] showed that carvacrol is able to embrittle and depolarize the cytoplasmic membrane.…”
Section: Resultssupporting
confidence: 92%
“…However, weak activity was observed when the EOs containing ketone or esters such as β-myrcene, α-thujone or gerenyl acetate [27,28]. Thus, previous findings showed that the T. capitaus EO has very significant antibacterial activity compared to the other tested EOs, which might be due to its major constituents: thymol and carvacrol [17,[29][30][31]. In previous studies, we demonstrated that thymol (81.49%), α-cubebene (3.44%), α-terpinene (3.83%) and β-ocimene (3.16%) were identified as the major components of T. capitatus [30].…”
Section: Antibacterial Effect Of Essential Oilsmentioning
confidence: 97%
“…and S. aureus CFSA2. Similarly, it was found that Bacillus cereus (ATCC10876), Micrococcus luteus (NRLL B-4375), and Proteus mirabilis (ATCC35659) were inhibited at 2.34, 7.03, and 4.68 mg/mL, respectively, of the EO extracted from the aerial parts of T. algeriensis growing in the north of Tunisia [ 68 ]. In addition, Zaïri et al revealed that the best antibacterial activity was obtained using the EO from T. algeriensis leaves (MIC = 0.5 mg/mL) which also inhibited the fungus Aspergillus flavus by up to 42.86% [ 69 ].…”
Section: In Vitro Pharmacological Propertiesmentioning
confidence: 99%
“…Consequently, generally high concentrations of EO are required for effective antimicrobial action to ensure the desired product shelf-life. Because of the intense aroma of EOs, this could lead to alteration of the product's sensory attributes, further limiting their application in food [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in meats, the use of EOs contributed to pathogen control, hence reducing the risk of foodborne outbreaks and ensuring safe meat products for the consumers [11,12]. However, the hydrophobic nature of EOs and their high reactivity with product matrix represent a huge challenge for their direct incorporation into food products [13].…”
Section: Introductionmentioning
confidence: 99%